Organophosphate-resistant forms of acetylcholinesterases in two scallops- the Antarctic Adamussium colbecki and the Mediterranean Pecten jacobaeus - ROMANI, R.; CORSI, I.; BONACCI, S.; FOCARDI, S.; DE MEDIO, G. E.; DE SANTIS, A.; INCARNATO, F.; GIOVANNINI, E.; ROSI, G. (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2006)
We describe the acetylcholinesterase polymorphisms of two bivalve molluscs, Adamussium colbecki and Pecten jacobaeus. The research was aimed to point out differences in the expression of pesticide-resistant acetylcholinesterase forms in organisms living in different ecosystems such as the Ross Sea (Antarctica) and the Mediterranean Sea. In A. colbecki, distinct acetylcholinesterase molecular forms were purified and characterized from spontaneously soluble, low-salt-soluble and low-salt-Triton extracts from adductor muscle and gills. They consist of two non-amphiphilic acetylcholinesterases (G2, G4) and an amphiphilic-phosphatidylinositol-membrane-anchored form (G2); a further amphiphilic-low-salt-soluble G2 acetylcholinesterase was found only in adductor muscle. In the corresponding tissues of P. jacobaeus, we found a non-amphiphilic G4 and an amphiphilic G2 acetylcholinesterase; amphiphilic-low-salt-soluble acetylcholinesterases (G2) are completely lacking. Such results are related with differences in cell membrane lipid compositions. In both scallops, all non-amphiphilic AChEs are resistant to used pesticides. Differently, the adductor muscle amphiphilic forms are resistant to carbamate eserine and organophosphate diisopropylfluorophosphate, but sensitive to organophoshate azamethiphos. In the gills of P. jacobaeus, amphiphilic G2 forms are sensitive to all three pesticides, while the corresponding forms of A. colbecki are sensitive to eserine and diisopropylfluorophosphate, but resistant to azamethiphos. Results indicate that organophosphate and/or carbamate resistant AChE forms are present in species living in far different and far away environments. The possibility that these AChE forms could have ensued from a common origin and have been spread globally by migration is discussed. © 2006 Elsevier Inc. All rights reserved.